PRINSIP SALING TOLERANSI (TASAMUH) PADA RESTORAN ALL YOU CAN EAT MENURUT PERSPEKTIF ISTIHSAN - hanik, umi atia (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
This study aims to determine the principle of mutual tolerance (tasamuh) in the all you can eat restaurant from the istihsan perspective. The research method used in this research (library research) is a qualitative approach. The data sources of this research are books and journals that are analyzed using the Miles and Huberman analysis method which includes three lines, namely data reduction, data presentation and drawing conclusions or verification. The results of this study conclude that the principle of mutual tolerance (tasamuh) in all you can eat restaurant according to the istihsan perspective is allowed based on ‘urf because it has become a habit of today’s society which will be difficult to avoid but still we should not go to waste in taking food because it is hated by god.Keywords: Buying and Selling, tasamuh, istihsan